Genetic Inactivation of Chlamydia trachomatis Inclusion Membrane Protein CT228 Alters MYPT1 Recruitment, Extrusion Production, and Longevity of Infection - Shaw, Jennifer H.; Key, Charlotte E.; Snider, Timothy A.; Sah, Prakash; Shaw, Edward I.; Fisher, Derek J.; Lutter, Erika I. (Frontiers in Cellular and Infection Microbiology, 2018)
Chlamydia trachomatis is an obligate intracellular pathogen with global health and economic impact. Upon infection, C. trachomatis resides within a protective niche, the inclusion, wherein it replicates and usurps host cell machinery and resources. The inclusion membrane is the key host-pathogen interface that governs specific protein-protein interactions to manipulate host signaling pathways. At the conclusion of the infection cycle, C. trachomatis exits the host cell via lysis or extrusion. Extrusion depends on the phosphorylation state of myosin light chain 2 (MLC2); the extent of phosphorylation is determined by the ongoing opposing activities of myosin phosphatase (MYPT1) and myosin kinase (MLCK). Previously, it was shown that MYPT1 is recruited to the inclusion and interacts with CT228 for regulation of host cell egress. In this study, we generated a targeted chromosomal mutation of CT228 (L2-ΔCT228) using the TargeTron system and demonstrate a loss of MYPT1 recruitment and increase in extrusion production in vitro. Mutation of CT228 did not affect chlamydial growth in cell culture or recruitment of MLC2. Moreover, we document a delay in clearance of L2-ΔCT228 during murine intravaginal infection as well as a reduction in systemic humoral response, relative to L2-wild type. Taken together, the data suggest that loss of MYPT1 recruitment (as a result of CT228 disruption) regulates the degree of host cell exit via extrusion and affects the longevity of infection in vivo.